2018
DOI: 10.1098/rsta.2018.0269
|View full text |Cite
|
Sign up to set email alerts
|

Designing bioinspired surfaces for water collection from fog

Abstract: One contribution of 14 to a theme issue 'Bioinspired materials and surfaces for green science and technology'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(88 citation statements)
references
References 17 publications
3
85
0
Order By: Relevance
“…The curvature gradient along the cones produces Laplace pressure gradient responsible for the movement of droplets. Several investigations have been carried out to mimic the conical spines in order to increase the water collection rate from fog [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The curvature gradient along the cones produces Laplace pressure gradient responsible for the movement of droplets. Several investigations have been carried out to mimic the conical spines in order to increase the water collection rate from fog [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…2 Then, fog collection from the atmosphere has been widely considered by researchers, [3][4][5][6][7][8] and it is an effective way to overcome water scarcity in arid and semi-arid areas. [9][10][11][12] Hence, various biomimetic fog collection materials inspired by the Namib desert beetle, [13][14][15][16][17] Cactus, [18][19][20] Nepenthes [21][22][23] and Spider silk [24][25][26][27] have gained considerable attention recently. For instance, Chen et al 28 provided a superhydrophilic/superhydrophobic hybrid lm inspired by the Namib desert beetle, and this hybrid lm coated with Ag/TiO 2 nanoparticles exhibited excellent water collecting ability.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that when collecting water from fog, other factors also play a role in droplet movement. These other factors are gravity and droplet coalescence [5,6]. The roles played by Laplace pressure gradient, gravity and coalescence need to be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…This pressure gradient within the droplet facilitates droplet movement toward the base of the spine where it can be collected by the cactus. There have been numerous attempts to create a water collector inspired by the cactus [2][3][4][5][6][7][8]. These studies have found that a cone or a triangular pattern is able to transport water droplets to its base because of a curvature gradient creating a Laplace pressure gradient inside of the droplets.…”
Section: Introductionmentioning
confidence: 99%